Marmosets as a preclinical model for testing “off-label” use of doxycycline to turn on Flt3L expression from high-capacity adenovirus vectors - VanderVeen, Nathan (Nature Publishing Group, 2014)
We developed a combined conditional cytotoxic, i.e., herpes simplex type 1-thymidine kinase (TK), plus immune-stimulatory, i.e., fms-like tyrosine kinase ligand-3–mediated gene therapy for glioblastoma multiforme (GBM). Therapeutic transgenes were encoded within high-capacity adenoviral vectors (HC-Ad); TK was expressed constitutively, while Flt3L was under the control of the TetOn regulatable promoter. We previously assessed efficacy and safety in intracranial GBM rodent models. But, since this approach involves expression of a cytokine within the brain, we chose the nonhuman primate, i.e., Callithrix jaccus (marmoset) as it has been established that its immune response shares similarities with man. We characterized the safety, cell-type specific expression, and doxycycline (DOX)-inducibility of HC-Ad-TetOn-Flt3L delivered within the striatum. We used allometrically scaled DOX doses delivered orally, twice daily for one month, mimicking the route and duration of DOX administration planned for the GBM trial. Flt3L was effectively expressed within astrocytes, microglia, oligodendrocytes, and neurons. No evidence of brain or systemic toxicities due to the treatment was encountered. Our data indicate that DOX doses equivalent to those used in humans to treat infections can be safely used “off-label” to turn “on” therapeutic gene expression from HC-Ad-TetOn-Flt3L; providing evidence for the safety of this approach in the clinic.